Commodification of Tri Datu Bracelets Talisman in Balinese Community (Universitas Negeri Semarang, 2017)
This article is the result of qualitative research with critical paradigm on two issues, the meaning of tri datu bracelet talisman as well as commodities and reasons of its use. Informants were set purposively, i.e. tri datu bracelet talisman makers, sellers, users, and religious leaders. Data collection techniques were interview, observation and document study. The data analysis followed the steps of conceptualization, the results of conceptualization, verification, and objectivation. The results show that the commodification of tri datu bracelet talisman created commodity or popular tri datu bracelet talisman refers to its position as an artifact for the fulfillment of human basic needs on security. This situation raises the creative industries of tri datu bracelet talisman. The use of this talisman is associated with the meaning of tri datu = Tri Murti = Tri Sakti = Om = Ganesha and reinforced by Pancadewata = kepeng (ancient coin). Therefore, its magical power becomes a supreme power in order to overcome danger from niskala (bhuta Kala and black magic). The joy of wearing this talisman is not only because it is easy to buy, but also because the Balinese still believe in its magical power. More importantly, Tri datu bracelet is also the identity of Balinese ethnic as the identity of hope and resistance in the context of Ajeg Bali movement.